A high thermal conductivity polyimide composite material and its preparation method and application in printers and copiers
Through the combination of specific thermal fillers and polyimide resin, the problem of limited room for improving thermal conductivity of the polyimide fixing belt is solved, which significantly improves the mechanical properties, realizes the optimization of the printer fixing speed and temperature, and improves production efficiency.
Patent Information
- Application Number
- CN202310221549.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-09
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-03-09
AI Technical Summary
The existing polyimide fixing belt has limited room for improving thermal conductivity in printers and copiers, resulting in low mechanical properties, short life, and poor bonding of high fillers and resins, making it difficult to meet the needs of efficient fixing.
Using specific thermal conductivity fillers, react with sodium hydroxide and carbon nanofibers, grafted with unsaturated fatty acids, and crosslinked with 1,2,4-trivinylcyclohexane to form modified carbon nanofibers and combine with polyamides. Amine resin prepares highly thermally conductive polyimide composites to increase thermal conductivity and mechanical properties.
It significantly improves the thermal conductivity and mechanical properties of polyimide composite materials, shortens the printer power supply waiting time, reduces power consumption, realizes the rapidity of fixing speed and the low temperature of fixing temperature, and improves production efficiency.
Smart Images

Figure FDA0005079417090000011 
Figure GDA0005079417100000021 
Figure GDA0005079417100000031
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polyimide materials, and in particular relates to a high thermal conductivity polyimide composite material and a preparation method thereof and application of the composite material in printers and copiers. Background Art
[0002] The processing of imaging devices such as printers and copiers includes a step of thermal fixing, in which the printed material to which the colorant image has been transferred passes through a fixing belt containing a heating source, the unfixed colorant is heated and melted, and the colorant is fixed to the transferred material, thereby forming an image.
[0003] The main material of the fixing belt is synthetic resin such as polyimide. In order to meet the demand for high thermal conductivity of the fixing belt, the existing technology usually adopts the method of increasing the content of thermal conductive fillers. However, the increase of thermal conductive fillers leads to a decrease in mechanical properties. It is necessary to add many retaining mechanisms in the fixing device and perform post-strengthening treatment on the ends to prevent deviation and maintain printing performance. Therefore, the existing fixing belt products have the defects of low mechanical properties and short life. At the same time, the high filler and resin bonding is poor, which leads to little room for improvement in the thermal conductivity of the product.
[0004] In summary, there is an urgent need to develop a new technical solution to solve the problems existing in the existing technology and meet the development needs of the current market. Summary of the invention
[0005] Based on this, it is of great significance to adopt appropriate methods to improve the thermal conductivity and mechanical properties of polyimide materials to ensure the efficient operation of equipment. The present invention prepares a high thermal conductivity polyimide composite material by compounding specific thermal conductive fillers, additives and polyimide resins, which greatly improves the mechanical properties of the product while ensuring the thermal conductivity of the composite material, overcomes the shortcomings of the prior art, and has good application prospects.
[0006] An object of the present invention is to provide a high thermal conductivity polyimide composite material, wherein the high thermal conductivity polyimide composite material comprises the following components in parts by weight:
[0007] Polyimide resin 80-150 parts
[0008] 10-30 parts of the first thermal conductive filler
[0009] 1-10 parts of additives;
[0010] The general structural formula of the polyimide resin is as follows:
[0011]
[0012] The first thermally conductive filler is obtained by reacting hydroxylated carbon nanofibers grafted with unsaturated fatty acids with 1,2,4-trivinylcyclohexane;
[0013] The unsaturated fatty acid is selected from one or more of oleic acid, linoleic acid, linolenic acid and arachidonic acid.
[0014] Furthermore, the preparation method of the first thermally conductive filler comprises the following steps:
[0015] S1. Adding carbon nanofibers to a sodium hydroxide solution, ultrasonically treating, adding hydrogen peroxide, stirring the reaction for 8-10 hours, washing, and drying to obtain hydroxylated carbon nanofibers;
[0016] S2. adding the hydroxylated carbon nanofibers to an unsaturated fatty acid solution, heating the reaction, washing and drying to obtain an intermediate product;
[0017] S3. Add the intermediate product, 1,2,4-trivinylcyclohexane and a catalyst into a reaction kettle, and heat to react to obtain the first thermally conductive filler.
[0018] Furthermore, in step S1, the concentration of the sodium hydroxide solution is 5-10 mol / L.
[0019] Furthermore, in step S2, the mass ratio of the hydroxylated carbon nanofibers to the unsaturated fatty acid is (50-150):1.
[0020] Furthermore, in step S3, the mass ratio of the intermediate product to 1,2,4-trivinylcyclohexane is (5-30):(1-5).
[0021] Furthermore, in step S3, the catalyst is dibenzoyl peroxide.
[0022] Furthermore, the high thermal conductivity polyimide composite material also includes a second thermally conductive filler, and the second thermally conductive filler is selected from one or more of silicon dioxide, aluminum oxide, silicon carbide, black lead, boron nitride, magnesium oxide, zinc oxide, aluminum nitride, and graphene.
[0023] Furthermore, the mass fraction of the second thermally conductive filler is 10-20 parts.
[0024] Furthermore, the n is selected from 4-1000.
[0025] Furthermore, the auxiliary agent is selected from one or more of a wetting agent, a leveling agent, a defoaming agent, a humectant, a mildewproofing agent, a thickener, and a viscosity reducer.
[0026] Another object of the present invention is to provide a method for preparing the above-mentioned high thermal conductivity polyimide composite material, comprising the following steps:
[0027] The polyimide resin, the thermal conductive filler and the auxiliary agent are uniformly mixed and then subjected to a thermal forming process to obtain the high thermal conductive polyimide composite material.
[0028] Another object of the present invention is to provide the use of the high thermal conductivity polyimide composite material as a fixing film in a printer or a copier.
[0029] The beneficial effects of the present invention are:
[0030] 1. The high thermal conductivity polyimide composite material of the present invention uses a specific material as the first thermal conductive filler. The thermal conductive filler first uses sodium hydroxide to react with carbon nanofibers, and introduces a large number of hydroxyl functional groups on the surface of the carbon nanofibers. On the one hand, the compatibility of the carbon nanofibers is enhanced, and on the other hand, the carbon nanofibers can be subjected to subsequent reactions and further grafted with unsaturated fatty acids. Long chains containing carbon-carbon double bonds are introduced into the modified carbon nanofibers after grafting, so that they are easy to crosslink and combine with 1,2,4-trivinylcyclohexane to form a more stable and better dispersed structure. When applied to polyimide resin, it can give the composite material stronger thermal conductivity and mechanical properties. It is surprisingly found that when arachidonic acid is used as a modifier for the reaction, the various properties of the product are significantly improved, which is significantly better than the existing technical solutions and has good application prospects.
[0031] 2. The use of the high thermal conductivity polyimide composite material provided by the present invention as a substrate to prepare a fixing film can shorten the waiting time after the printer power is turned on, reduce power consumption, thereby achieving a high fixing speed and a low fixing temperature. At the same time, due to the improvement of mechanical strength, the fixing property is better, which greatly improves production efficiency. DETAILED DESCRIPTION
[0032] In order to more clearly illustrate the technical solution of the present invention, the following examples are listed. Unless otherwise stated, the raw materials, reactions and post-treatment methods shown in the examples are common raw materials on the market and technical methods well known to those skilled in the art.
[0033] The carbon nanofibers in the embodiments of the present invention were purchased from Teijin Company "PotenCia".
[0034] The additives in the embodiment of the present invention include a defoamer, a wetting agent, and a leveling agent in a mass ratio of 1:1:1. The defoamer is Taoxi silicone oil FZ-2110; the wetting agent is Shengbang silicone oil SI-2047; and the leveling agent is DISPARLON L1980N.
[0035] In the embodiment of the present invention, the polyimide resin is purchased from Du Pont Company "Kapton", and its structural formula is
[0036]
[0037] Among them, n is 4.
[0038] Example 1
[0039] A high thermal conductivity polyimide composite material comprises the following components in parts by weight:
[0040] 80 parts of polyimide resin
[0041] 10 parts of the first thermal conductive filler
[0042] 1 part of additive.
[0043] The preparation method of the first thermally conductive filler comprises the following steps:
[0044] S1. 1 g of carbon nanofibers was added to 400 mL of 10 mol / mL sodium hydroxide solution, and after ultrasonic dispersion for 40 min, 3 mL of 30% hydrogen peroxide was added as a catalyst, and the mixture was stirred for 10 h. After centrifugation to remove the upper liquid, the mixture was washed with distilled water until neutral, and dried to obtain hydroxylated carbon nanofibers;
[0045] S2. adding the hydroxylated carbon nanofibers to an oleic acid solution (hydroxylated carbon nanofibers: oleic acid = 100:1, m / m), reacting at 30° C. for 10 min, filtering, washing, and drying to obtain an intermediate product;
[0046] S3. Add the intermediate product, 1,2,4-trivinylcyclohexane and dibenzoyl peroxide into a reaction kettle (intermediate product: 1,2,4-trivinylcyclohexane: dibenzoyl peroxide = 30:3:1, m / m / m), react at 120° C. for 2 hours to obtain the first thermally conductive filler.
[0047] The preparation method of the above-mentioned high thermal conductivity polyimide composite material comprises the following steps:
[0048] According to the above mass fractions, the polyimide resin, the first thermal conductive filler and the auxiliary agent are mixed and stirred uniformly, and then treated at 80° C. for 1 hour, 180° C. for 1 hour, and then at 310° C. for 1 hour. After cooling, the high thermal conductive polyimide composite material is obtained.
[0049] Example 2
[0050] A high thermal conductivity polyimide composite material comprises the following components in parts by weight:
[0051]
[0052] The preparation method of the first thermally conductive filler comprises the following steps:
[0053] S1. 1 g of carbon nanofibers was added to 400 mL of 10 mol / mL sodium hydroxide solution, and after ultrasonic dispersion for 40 min, 3 mL of 30% hydrogen peroxide was added as a catalyst, and the mixture was stirred for 10 h. After centrifugation to remove the upper liquid, the mixture was washed with distilled water until neutral, and dried to obtain hydroxylated carbon nanofibers;
[0054] S2. adding the hydroxylated carbon nanofibers to a linoleic acid solution (hydroxylated carbon nanofibers: linoleic acid = 100:1, m / m), reacting at 40° C. for 15 min, filtering, washing, and drying to obtain an intermediate product;
[0055] S3. Add the intermediate product, 1,2,4-trivinylcyclohexane and dibenzoyl peroxide into a reaction kettle (intermediate product: 1,2,4-trivinylcyclohexane: dibenzoyl peroxide = 30:3:1, m / m / m), react at 120° C. for 2 hours to obtain the first thermally conductive filler.
[0056] The preparation method of the above-mentioned high thermal conductivity polyimide composite material comprises the following steps:
[0057] According to the above mass fractions, the polyimide resin, the first thermal conductive filler, aluminum oxide and the additive are mixed and stirred uniformly, and then treated at 80° C. for 1 hour, 180° C. for 1 hour, and then at 310° C. for 1 hour. After cooling, the high thermal conductive polyimide composite material is obtained.
[0058] Example 3
[0059] A high thermal conductivity polyimide composite material comprises the following components in parts by weight:
[0060]
[0061] The preparation method of the first thermally conductive filler comprises the following steps:
[0062] S1. 1 g of carbon nanofibers was added to 400 mL of 10 mol / mL sodium hydroxide solution, and after ultrasonic dispersion for 40 min, 3 mL of 30% hydrogen peroxide was added as a catalyst, and the mixture was stirred for 10 h. After centrifugation to remove the upper liquid, the mixture was washed with distilled water until neutral, and dried to obtain hydroxylated carbon nanofibers;
[0063] S2. adding the hydroxylated carbon nanofibers to an arachidonic acid solution (hydroxylated carbon nanofibers: arachidonic acid = 50:1, m / m), reacting at 40° C. for 15 min, filtering, washing, and drying to obtain an intermediate product;
[0064] S3. Add the intermediate product, 1,2,4-trivinylcyclohexane and dibenzoyl peroxide into a reaction kettle (intermediate product: 1,2,4-trivinylcyclohexane: dibenzoyl peroxide = 30:3:1, m / m / m), react at 120° C. for 2 hours to obtain the first thermally conductive filler.
[0065] The preparation method of the above-mentioned high thermal conductivity polyimide composite material comprises the following steps:
[0066] According to the above mass fractions, the polyimide resin, the first thermal conductive filler, silicon carbide and the auxiliary agent are mixed and stirred uniformly, and then treated at 80° C. for 1 hour, 180° C. for 1 hour, and then at 310° C. for 1 hour. After cooling, the high thermal conductive polyimide composite material is obtained.
[0067] Comparative Example 1
[0068] A polyimide composite material, the difference between this comparative example and Example 3 is that: in the preparation method of the first thermally conductive filler, step S1 is not performed, and carbon nanofibers are directly reacted with arachidonic acid and then reacted with 1,2,4-trivinylcyclohexane, and other materials and preparation methods are the same as those in Example 3.
[0069] Comparative Example 2
[0070] A polyimide composite material. The difference between this comparative example and Example 3 is that unmodified carbon nanofibers are used as the first thermal conductive filler, and other materials and preparation methods are the same as those of Example 3.
[0071] Test Example 1
[0072] The performance of the high thermal conductivity polyimide composite materials prepared in the examples and comparative examples was tested.
[0073] Test method:
[0074] Thermal conductivity was determined using the thin film thermal diffusivity tester M3 from ai-Phase. The thermal conductivity was calculated by multiplying the obtained thermal diffusivity with the specific heat and density of the polyimide.
[0075] Fixability test method: Fix the polyimide carbon nanofiber on an aluminum plate. Sprinkle toner on the polyimide carbon nanofiber and heat the sample to 150°C. Press the paper on the toner and rub it about 5 times, then tear off the paper to confirm whether the toner is transferred to the paper and evaluate according to the following standards. Excellent: The toner is completely transferred to the paper; Acceptable: Most of the toner is transferred to the paper; Unacceptable: A lot of toner remains on the polyimide carbon nanofiber.
[0076] Offset test: The polyimide carbon nanofibers are loaded into the fuser and the offset is evaluated according to the following criteria. Pass: No offset occurs; Fail: Offset occurs.
[0077] Measurement of axial and circumferential tensile growth rate and tensile modulus, measuring device: AG-IS manufactured by Shimadzu Corporation; measuring method: fix the upper and lower parts of the polyimide sample (10mm*100mm), measure the tensile growth rate and tensile modulus at a tensile speed of 1.7mm / s and a distance of 50mm between the upper and lower clamps.
[0078] The test results are shown in Table 1.
[0079] Table 1 Performance test results
[0080]
[0081] According to Table 1, it can be concluded that the specific first thermal conductive filler is used in the high thermal conductive polyimide composite materials prepared in Examples 1-3 of the present invention, which effectively improves the thermal conductivity and mechanical properties of the products, especially the hydroxylated carbon nanofibers modified by arachidonic acid and 1,2,4-trivinylcyclohexane. The improvement of various properties is the most significant. However, since the carbon nanofibers are not hydroxylated in Comparative Example 1, it is difficult to graft unsaturated fatty acids, and only a small amount is adsorbed on the surface of the carbon nanofibers, making it difficult to carry out subsequent reactions, and the performance improvement effect is not ideal; Comparative Example 2 uses unmodified carbon nanofibers, and its various properties are relatively poor. In summary, the high thermal conductive polyimide composite material of the present invention has good application prospects in the fields of fixing films and the like.
[0082] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0083] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A high thermal conductivity polyimide composite material, characterized in that: The high thermal conductivity polyimide composite material comprises the following components in parts by mass: Polyimide resin 80-150 parts 10-30 parts of the first thermal conductive filler 1-10 parts of additives; Wherein, the general structural formula of the polyimide resin is as follows: The n is selected from 4-1000; The first thermally conductive filler is obtained by reacting hydroxylated carbon nanofibers grafted with unsaturated fatty acids with 1,2,4-trivinylcyclohexane; The unsaturated fatty acid is selected from one or more of oleic acid, linoleic acid, linolenic acid, and arachidonic acid; The preparation method of the first thermally conductive filler comprises the following steps: S1. Adding carbon nanofibers to a sodium hydroxide solution, ultrasonically treating, adding hydrogen peroxide, stirring the reaction for 8-10 hours, washing, and drying to obtain hydroxylated carbon nanofibers; S2. adding the hydroxylated carbon nanofibers to an unsaturated fatty acid solution, heating the reaction, washing and drying to obtain an intermediate product; S3. adding the intermediate product, 1,2,4-trivinylcyclohexane and the catalyst into a reactor, heating the reaction to obtain the first thermally conductive filler; In step S2, the mass ratio of the hydroxylated carbon nanofibers to the unsaturated fatty acid is (50-150):1; In step S3, the mass ratio of the intermediate product to 1,2,4-trivinylcyclohexane is (5-30):(1-5).
2. The high thermal conductivity polyimide composite material according to claim 1, characterized in that: In step S1, the concentration of the sodium hydroxide solution is 5-10 mol / L.
3. The high thermal conductivity polyimide composite material according to claim 1, characterized in that: The high thermal conductivity polyimide composite material also includes a second thermal conductive filler, which is selected from one or more of silicon dioxide, aluminum oxide, silicon carbide, black lead, boron nitride, magnesium oxide, zinc oxide, aluminum nitride, and graphene.
4. The high thermal conductivity polyimide composite material according to claim 1, characterized in that: The auxiliary agent is selected from one or more of a wetting agent, a leveling agent, a defoaming agent, a humectant, a mildewproofing agent, a thickener, and a viscosity reducer.
5. The method for preparing the high thermal conductivity polyimide composite material according to any one of claims 1 to 4, characterized in that: The steps include: The polyimide resin, the thermal conductive filler and the auxiliary agent are uniformly mixed and then subjected to a thermal forming process to obtain the high thermal conductive polyimide composite material.
6. Use of the high thermal conductivity polyimide composite material according to any one of claims 1 to 4 as a fixing film in a printer or a copier.
Citation Information
Patent Citations
Carbon fiber reinforced polyimide composite material and preparation method thereof
CN103483816A
Polyimide film and preparation method thereof
CN111253602A